Kinesics Gender Dimension as a Dominant of Nonverbal Communication in the Volodymyr Lys's Works (Linguostylistic Studies, 2020)
The article highlights the specific features of the kinesics means of communication in the novel by Volodymyr Lys Solo for Solomiya. The author distinguishes the basic categories of kinesics explication in the novel, namely facial expressions, gestures, body movements, postures. The author uses mainly verbs to pout, to twitch, to inflate, to cover, to whisper, to kiss, to put, to stir, to wipe, to rub, to bite, to chew for a detailed description of the kinesics parameters of nonverbalism expressed by kinemes of lips, mouth. Often, semiotically significant movements in a literary work are detailed by identifiers (adjectives and adverbs).The study has revealed that the kinesics component of nonverbalism in the text is mostly actualized in the constructions with adapters of the upper body: head (ear, eye, pupil, forehead, cheek, nose, chin, tongue, tooth, hair, face, temple, forehead), neck, shoulder, chest, heart, belly, side, waist, nape, back, hand (elbow, wrist, fist, finger, palm, nail) and lower body: leg (thigh, knee, calf).In the focus of attention is gender differentiation of components of kinesics in the literary text. Dominant are typical female gestures and poses: hands to the sides (demonstration of militant intentions, conflict), clap your hands (manifestation of joy), put the head on the shoulder (tenderness), blink the eyes (a sign of confusion), put a finger on the lips (call to silence), cover the mouth with a hand (restraint in the manifestation of the reactions), hide the face in a pillow or press a face against the pillow  (expressing shyness), wave the hips, beckon with a finger, scratch with a fingernail (display of flirtation, coquetry), stomp a foot (manifestation of dissatisfaction, aggression), bend the knees almost under the chin (protective posture), etc.The author often uses different types of gestures and movements without adapters to describe the nonverbal communication of the characters: a) gestures of a tactile nature; b) gestures and movements caused by the inner state, as a fleeting expression of emotions; c) gestures to indicate a situationally forced action, etc. Verbalizing female kinetic behavior, V. Lisi uses gestures, movements, reactions of the metaphorical type.The facial expression has clear gender features among the indicators of internal emotional states used by the author to portray the characters. Naturally, women are more likely to express their emotions and show them openly. In the analyzed text, such mimicry means of non-verbalisation as a smile is, definitely, gender differentiating.Selection of the units of kinesics verbalization and the means of their imagery intensification in the literary text is predetermined by peculiarities of the psychological portrayal of characters and the theme of the work.
Keywords: nonverbal communication,; kinesics,; verbalization,; female communicative behavior,; male communicative behavior,; artistic text.